Brain function in carriers of a genome-wide supported bipolar disorder variant - Erk, Susanne; Meyer-Lindenberg, Andreas; Schnell, Knut; Opitz von Boberfeld, Carola; Esslinger, Christine; Kirsch, Peter; Grimm, Oliver; Arnold, Claudia; Haller, Leila; Witt, Stephanie; Cichon, Sven; Nöthen, Markus Maria; et al. (Archives of general psychiatry, 2010)
The neural abnormalities underlying genetic risk for bipolar disorder, a severe, common, and highly heritable psychiatric condition, are largely unknown. An opportunity to define these mechanisms is provided by the recent discovery, through genome-wide association, of a single-nucleotide polymorphism (rs1006737) strongly associated with bipolar disorder within the CACNA1C gene, encoding the α subunit of the L-type voltage-dependent calcium channel Cav1.2.To determine whether the genetic risk associated with rs1006737 is mediated through hippocampal function.Functional magnetic resonance imaging study.University hospital.A total of 110 healthy volunteers of both sexes and of German descent in the Hardy-Weinberg equilibrium for rs1006737.Blood oxygen level-dependent signal during an episodic memory task and behavioral and psychopathological measures.Using an intermediate phenotype approach, we show that healthy carriers of the CACNA1C risk variant exhibit a pronounced reduction of bilateral hippocampal activation during episodic memory recall and diminished functional coupling between left and right hippocampal regions. Furthermore, risk allele carriers exhibit activation deficits of the subgenual anterior cingulate cortex, a region repeatedly associated with affective disorders and the mediation of adaptive stress-related responses. The relevance of these findings for affective disorders is supported by significantly higher psychopathology scores for depression, anxiety, obsessive-compulsive thoughts, interpersonal sensitivity, and neuroticism in risk allele carriers, correlating negatively with the observed regional brain activation.Our data demonstrate that rs1006737 or genetic variants in linkage disequilibrium with it are functional in the human brain and provide a neurogenetic risk mechanism for bipolar disorder backed by genome-wide evidence.